Digital Healthcare and Expertise Mental Health and New Knowledge Practices - Egher, Claudia (Health, Technology and Society, 2023)
This open access book explores how expertise about bipolar disorder is performed on American and French digital platforms by combining insights from STS, medical sociology and media studies. It addresses topical questions, including: How do different stakeholders engage with online technologies to perform expertise about bipolar disorder? How does the use of the internet for processes of knowledge evaluation and production allow for people diagnosed with bipolar disorder to reposition themselves in relation to medical professionals? How do cultural markers shape the online performance of expertise about bipolar disorder? And what individualizing or collectivity-generating effects does the internet have in relation to the performance of expertise? The book constitutes a critical and nuanced intervention into dominant discourses which approach the internet either as a quick technological fix or as a postmodern version of Pandora's box, sowing distrust among people and threatening unified conceptualizations and organized forms of knowledge.